Adding household surveys to the behavioral economics toolbox: insights from the SOEP innovation sample - Urs Fischbacher; Levent Neyse; David Richter; Carsten Schröder (Journal of the Economic Science Association, 2024)
While laboratory and field experiments are the major items in the toolbox of behavioral economists, household panel studies can complement them and expand their research potential. We introduce the German Socio-Economic Panel's Innovation Sample (SOEP-IS), which offers researchers detailed panel data and the possibility to collect personalized experimental and survey data for free. We discuss what SOEP-IS can offer to behavioral economists and illustrate a set of design ideas with examples. Although we build our discussion on SOEP-IS, our purpose is to provide a guide that can be generalized to other household panel studies as well.
Keywords: C83; C9; D1; D9; 330; Experiments; Household survey; Panel study; Economic methods; Economic preferences; Behavioral economics; SOEP